Vagrancy and Beggaring – From Necessity to Extortion: Socially Pathological and Criminological Character - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
For centuries now, vagrants and beggars have been a problem in every social environment, that is, a small part of each social community that could not fit into or get accustomed to its own social surroundings. They have, therefore, since they had to live and survive, constantly been looking for their "happiness" in new and newer surroundings and communities, without any support or residence among local people. However, they have always counted on the charity and empathy of known and unknown people around them, and, to that matter, resorted to some kind of emphasis on the looks of their problem – dirty and worn-out clothes, crippled limbs, smooth-talking, etc. With time, unfortunately, their misfortune had become a chance for an organised business of unscrupulous extortionists; hence, the criminalisation of this socially-pathological phenomenon is a subject of this work.